RIO GRANDE TURKEY NEST HABITAT SELECTION IN SOUTHWESTERN OREGON - Thomas W. Keegan; John A. Crawford (Wildlife Society Bulletin)
Abstract: We studied nest habitat selection and characteristics of extralimital Rio Grande wild turkeys (Meleagris gallopavo intermedia) in southwestern Oregon to provide information about this important component of wild turkey ecology and to identify forest management strategies that will optimize preferred nesting habitat. Between March 1989 and July 1991 we identified 126 nest sites of 55 radiomarked females that were part of a recently introduced population (<10 years) and quantified habitat at 3 spatial scales in a hierarchical approach. Only regenerating mixed‐conifer stands that were clearcut within 10 years were selected by nesting females (17% of observations, P < 0.05). Dense mature mixed conifer stands were used less than expected (P < 0.05) whereas meadows and dense sapling/pole conifer habitats were not used. Nest sites were characterized by dense horizontal screening (>93% from 0 to 30 cm above ground), understory vegetation >20 cm tall, and low shrubs covering 37 to 69% of nest sites. Land managers should implement forest management strategies that provide mosaics of relatively small regenerating stands, dense young conifer stands, and mixed hardwood/conifer woodland and savanna cover types with abundant understory vegetation including low shrubs to provide optimal nesting habitat for Rio Grande turkeys in the Oregon Cascade Range.